The Influence of Human Resource Development on Employee Performance at PT. Bukit Angkasa Makmur - Zery Try Nando; Ratnawili Ratnawili (Penerbit Jurnal Indonesia, 2023)
The purpose of this study is was to determine the effect of human resource development on employee performance at PT. Bukit Angkasa Makmur. several factors that will be discussed in this study, including Human Resource Development on Employee Performance at PT. Bukit Angkasa Makmur. The objects in this study are employees of PT. Bukit Angkasa Makmur numbered 174 people. Data collection techniques in research are observation and questionnaires.There are several data analysis techniques used in this study, including descriptive analysis, classic assumption test, simple regression analysis, coefficient of determination (R2) and hypothesis testing. Based on the research results, the following conclusions can be drawn: The results of research on Human Resource Development have a significant influence on Employee Performance at PT. Bukit Angkasa Makmur from the results obtained from the t-test results obtained a tsig value of 0.000 which is smaller than the significant level used, namely 0.05, then Ho is rejected, which means that Human Resource Development has a significant effect on Employee Performance at PT. Bukit Angkasa Makmur.